Uniform Crime Reports: County Level Detailed Arrest and Offense Data, 1985 and 1987 ([Verlag nicht ermittelbar], 1990)
The files in this collection contain counts of arrests and offenses in the United States for Part I and Part II offenses: murder, rape, robbery, assault, burglary, larceny, auto theft, arson, forgery, fraud, embezzlement, vandalism, weapons violations, sex offenses, drug and alcohol abuse violations, gambling, vagrancy, curfew, and runaways. County populations are also reported.